STRATEGY THE DEVELOPMENT OF THE USE OF ORGANIC FERTILIZER MAJATANI IN BALI PROVINCE - Meilani, Desi Rica; Nurliza, Nurliza; Kurniati, Dewi (Jurnal Sains Pertanian Equator, 2019)
Fertilizer majatani organic is shaped liquid and is a solution for agricultural development because, is environmentally friendly but not yet fully applied by farmers leading to the need for a strategy supporting the development of the use of fertilizer. Study aimsare1) Knowing factor internal and external rice farmers in Bali Province 2) Make a design development strategy the use of fertilizer organic majatani in Bali Province. Research was conducted in Dalang village subdistrict of Salemadeg Timur Tabanan regency of Bali Province by 30 respondents. The data collection was done through interviews directly to speakers with the help of the questionnaire. Data analysis was conducted using SWOT. The result showed that: 1.A strategy the development of the use of fertilizer organic majatani in Bali province are on a cell 1 which is a strategy to grow and build; 2.A strategy the development of the use of organic fertilizer majatani in bali province use strategy so, which is trying to preserve and enhance the quality of organic fertilizer majatani. Keyword: analysis SWOT, majatani , fertilizer organic , development , strategy